El Jaber, Loreley. Motines y traición en el Río de la Plata. Un ensayo sobre la voz de la plebe: Ciudad Autónoma de Buenos Aires, Tinta Limón Ediciones, 2025. 256 pp. ISBN: 978-6316507-31-0 - Landini, María Belén (Boletín de Literatura Comparada, 2026)
What happens when history is told not by the victors, but by the common people who witnessed the collapse of power? Motines y traición en el Río de la Plata (Tinta Limón, 2025), a groundbreaking work by researcher Loreley El Jaber, challenges the traditional narrative of the Spanish conquest. Moving beyond the rigid boundaries of a historical essay, El Jaber dives into the archives to rescue the voices of the "plebe"—the common sailors, soldiers, and women—whose testimonies in judicial trials shaped the fate of the most powerful men of their time.